If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2x-(2=4)(x+4)=6x
We move all terms to the left:
2x-(2-(4)(x+4))=0
We calculate terms in parentheses: -(2-4(x+4)), so:We get rid of parentheses
2-4(x+4)
determiningTheFunctionDomain -4(x+4)+2
We multiply parentheses
-4x-16+2
We add all the numbers together, and all the variables
-4x-14
Back to the equation:
-(-4x-14)
2x+4x+14=0
We add all the numbers together, and all the variables
6x+14=0
We move all terms containing x to the left, all other terms to the right
6x=-14
x=-14/6
x=-2+1/3
| –4x+5=17 | | 3n-81=15 | | (168)=(y) | | 1/2(2/5x+14)=12/3 | | 6x-2+72=30 | | u+14/8=3 | | -22=-5d-6d | | 10.76=1.3k+2.96 | | 1=v/5-3 | | (1)/(3)(x+1,632)=726 | | 2x+2(12.25)=57.5 | | 3.6w=2.8w+12 | | -18=7(4y-9) | | 5x-3+2x=3+6x | | (y+20)=(70) | | 3n-8n=7 | | 59x+354=7 | | 3/4n-10=1/2n+5 | | 20=a-296 | | -6-1x-2=1x-4x | | 28=-7+6(n+5) | | 10=k/3+9 | | d/2+45=60 | | 90+50=x | | 0.5+x/3=0.5/2 | | 28=-7+6(n=5 | | 9x-8=-1x= | | 296=a-20 | | m^2+32=41 | | 40+7.5x2x/100=10 | | 9(6-8f)=-15 | | 5x120=3x+40 |